Perinatal and Long Term Outcome of Monochorionic Twins Complicated by Twin-Twin Transfusion Syndrome - Casati, D.; Laoreti, A.; Faiola, S.; Lanna, M. (International Journal of Pediatrics and Child Health, 2021)
Twin-twin transfusion syndrome (TTTS) is the most harmful complication of monochorionic twin pregnancies. Fetoscopic laser coagulation of placental vascular anastomoses represents the causative and first-line treatment for the disease. Substantial improvements in survival rates and long-term outcome have been achieved during the last 20 years of practice. This is due to improvements in antenatal detection of the condition, surgical skills and centralization in the referral fetal therapy unit, as well as postnatal intensive care and follow up programs. Major morbidity issues concern cardiologic, renal and cerebral functions and are mainly caused by intrauterine haemodynamic imbalances and prematurity. This review summarizes the current evidence on the prognosis of monochorionic twins survivors after TTTS treated by laser surgery, focusing on perinatal and long-term outcomes.